2001
DOI: 10.1603/0046-225x-30.4.720
|View full text |Cite
|
Sign up to set email alerts
|

Differential Variation in Development of the B- and Q-Biotypes ofBemisia tabaci(Homoptera: Aleyrodidae) on Sweet Pepper at Constant Temperatures

Abstract: Developmental rates of the B-and Q-biotypes of Bemisia tabaci (Gennadius, 1889) were studied at seven constant temperatures (17, 20, 23, 26, 30, 33, and 35ЊC) on sweet pepper, Capsicum annuum L. (ÔMorró nÕ). The egg incubation period and the times required to complete development at all immature stages decreased with increasing temperature up to 33ЊC, but at 35ЊC were found to be greater than at 33ЊC. The relationships between developmental rate of B. tabaci and temperature were inßuenced by the insect bioty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
6
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 25 publications
8
88
6
6
Order By: Relevance
“…They believed that oviposition range of B. tabaci based on the temperature, host, plants and insect biotype was significantly variable and showed that the gross fecundity and fertility rates, gross hatch rate, and net fecundity and fertility rates were greater on rapeseed than on cotton. The developmental times of B biotype (22.28 d) reared on cotton in this study were nearly equal to those reared on cotton (23.6 d) and poinsettia (23.2 d) at about 25ºC (Bethke et al 1991) and on sweet pepper (21.5 d) at 26ºC (Muniz and Nombela 2001). The fecundity of B biotype reared on rapeseed (68 eggs) was higher than on cotton (51.2 eggs) (Bethke et al 1991) and less than on poinsettia (85.0 eggs) (Bethke et al 1991), tobacco (72.3 eggs) (Enkegaard 1993) at about 25ºC, and on alfalfa, broccoli, cantaloupe, cotton and zucchini (40.6 -70.6 eggs) at 27ºC (Yee and Toscano 1996).…”
Section: Discussionmentioning
confidence: 52%
“…They believed that oviposition range of B. tabaci based on the temperature, host, plants and insect biotype was significantly variable and showed that the gross fecundity and fertility rates, gross hatch rate, and net fecundity and fertility rates were greater on rapeseed than on cotton. The developmental times of B biotype (22.28 d) reared on cotton in this study were nearly equal to those reared on cotton (23.6 d) and poinsettia (23.2 d) at about 25ºC (Bethke et al 1991) and on sweet pepper (21.5 d) at 26ºC (Muniz and Nombela 2001). The fecundity of B biotype reared on rapeseed (68 eggs) was higher than on cotton (51.2 eggs) (Bethke et al 1991) and less than on poinsettia (85.0 eggs) (Bethke et al 1991), tobacco (72.3 eggs) (Enkegaard 1993) at about 25ºC, and on alfalfa, broccoli, cantaloupe, cotton and zucchini (40.6 -70.6 eggs) at 27ºC (Yee and Toscano 1996).…”
Section: Discussionmentioning
confidence: 52%
“…Linear or thermal summation U varo ν 1931, Wigglesworth 1953, Campbell et al 1974, Campbell and Mackauer 1975, Johnson et al 1979, Obrycki and Tauber 1982, Logan 1988, De Clerq and Degheele 1992, Lamb, 1992, Fomasari, 1995, Lactin and Johnson 1995, Stathas 2000, Muniz and Nombela 2001. , Lactin and Johnson 1995, Briere and Pracros 1998, Royer et' al.…”
Section: = κ/(Temp -T )mentioning
confidence: 99%
“…, Lactin and Johnson 1995, Briere and Pracros 1998, Royer et' al. 1999, Muniz and Nombela 2001, Tobin et al 2001, Roy et al 2002 In addition, the Linear model and the Lac tin model (Table 1) was used and the fol lowing standard thermal indices were cal culated:…”
Section: = κ/(Temp -T )mentioning
confidence: 99%
See 1 more Smart Citation
“…So, according to the method of Muñiz and Nombela (2001), a small cage was used for the bioassay study of T. vaporiorum; slight changes were made. Disposable glass was used.…”
Section: Making Sure That T Vaporariorum Insects Were Of the Same Bimentioning
confidence: 99%